ANALISIS CEMARAN LOGAM BERAT Pb DAN Cd PADA RUMPUT LAUT Eucheumacottonii DI DAERAH PERAIRAN KABUPATEN KOLAKA UTARA - Rachmin Munadi (Cokroaminoto Journal of Chemical Science, 2022)
Research has been carried out by the analysis of heavy metal contamination of Pb and Cd on Eucheuma cottonii seaweed in the waters of North Kolaka Regency. This study aims to determine the levels of heavy metals Pb and Cd by using atomic absorption spectrophotometry. Eucheuma cottonii seaweed samples were taken form three locations in the waters in the North Kolaka Regensy, namely samplen 1 in Kamisi village, sample 2 in Lawadia village, and samplie 3 in Watumea village. Samples were treated by washing with running water, cut it into small piaces, weighed as 4 grams, authored with an electric stove, baked in a furnace for 2 hours at a temperature of 500oC, seaweed ash cooled, after which 5 ml of concentrated HNO3 was added, added distilled water until the cup lip, put in a 50 ml volumetric flask and sufficient volume, filtered until clear, formed filtreate and residue. The filtrate was analyzed using Atomic Absorption Spectrophotometer at wavelengths of 283.2 nm and 228.9 nm for Pb and Cd. The results of the analysis showed that the Pb metal conted were 0.59 ppm, 0.89 ppm, 0.59 ppm for samples 1, 2 and 3, whereas for the Cd metal were 0.22 ppm, 0.25 ppm, 0,29 ppm for samples 1, 2 and 3. The results of the analysis exceeded the threshold value set by SNI in 2009, namely for metals Pb 0,5 ppm and Cd 0,22 ppm. So thet seawed originating from North Kolaka waters has been contaminatied with Pb and Cd metals and has the potential to cause accumulation in the human body if consumend in the long time.